Preferences to improve rounding efficiency amongst hospitalists: a survey analysis - Angela C. Mirabella; Nicole E. McAmis; Corey Kiassat; Richard Feinn; Gagan Singh (Greater Baltimore Medical Center, 2021)
Background: There is no 'gold standard' method of rounding for hospitalists. This study investigates hospitalist rounding preferences to improve efficiency based on resources categorized under work assignment and communication. Methods: An anonymous survey containing demographics and questions on preferences for rounding efficiently by hospitalists were widely distributed online. Responses were presented using descriptive statistics and SPSS v26. Results: There were 143 respondents, majority male (60%) with (40%) female. Most (80%) expect higher patient volumes when working with an advanced practitioner (AP). Half (50%) preferred rounding independently, (34%) with an AP, and majority (62%) with a resident. Geographic rounding was most efficient at 85%. Text messaging for paging was preferred (70.1%) to pagers (23.4%). Respondents preferred calling a consultant (52%) or text messaging (40%). Majority have not used a WOW yet (74%) believe WOWs could improve efficiency. Majority prefer dictation via Dragon (47%) to the phone application (23%). Only 29% believe their EMR is too complex to navigate. Preference difference due to age was insignificant. Discussion and Conclusion: In this study, 143 hospitalists provided preferences for improving rounding efficiency based on elements from work assignment and communication. This analysis can provide insights on designing best practices for hospitalists rounding efficiently.